Factors associated with poor outcome in fetuses prenatally diagnosed with sacrococcygeal teratoma. (5th August 2021) - van Heurn, Lieke J.; Coumans, Audrey B. C.; Derikx, Joep P. M.; Bekker, Mireille N.; Bilardo, Katia M.; Duin, Leonie K.; Knapen, Maarten F. C. M.; Pajkrt, Eva; Sikkel, Esther; van Heurn, L. W. Ernest; Oepkes, Dick
Abstract: Aim of the study: Outcome of fetuses, prenatally diagnosed with sacrococcygeal teratoma (SCT), is still poorly documented. This study assesses the incidence and prenatal predictors of outcome in all fetuses prenatally diagnosed with SCT. Methods: This is a retrospective study on all fetuses prenatally diagnosed with SCT from 1998 to 2018 in the Netherlands. Poor outcome was defined as terminations of pregnancy (TOP) because of expected unfavorable outcome, intrauterine fetal death, or early neonatal death. Potential risk factors for poor outcome were analyzed. Main results: Eighty‐four fetuses were included. Sixteen (19.0%) TOPs were excluded from statistical analysis. Eleven of the remaining 68 fetuses had poor outcome. Overall mortality was 32.1%, with a mortality excluding TOPs of 13.1%. Thirteen fetal interventions were performed in 11 (13.1%) fetuses. Potential risk factors for poor outcome were the presence of fetal hydrops (OR: 21.0, CI: 2.6–275.1, p  = 0.012) and cardiomegaly (OR: 10.3, CI: 1.9–55.8, p  = 0.011). Conclusions: The overall mortality of fetuses prenatally diagnosed with SCTs including tTOP was 32.1%. This high mortality rate was mainly due to termination of pregnancy. Mortality excluding TOP was 13.1%. Potential risk factors for poor outcome were fetal hydrops and cardiomegaly. Key points: What's already known about the topic? 50%–82% of sacrococcygeal teratomas (SCTs) are currently diagnosed in the prenatal period Perinatal mortality rate of prenatally diagnosed SCT varies between 13% and 50% High tumor volume index (TVI), fast SCT growth rate, and predominantly solid, highly vascularized tumors are factors predictive for poor outcome What does this study add? The incidence of patients prenatally diagnosed with SCT is approximately one in 35, 000 with a poor outcome in 13% Fetal hydrops and cardiomegaly are both risk factors for poor outcome in fetuses prenatally diagnosed with SCT